Consideration of Medical and Public Health Coordination - Experience from the 2016 Kumamoto, Japan Earthquake. Issue 2 (14th April 2019) - Kondo, Hisayoshi; Koido, Yuichi; Kawashima, Yuzuru; Kohayagawa, Yoshitaka; Misaki, Miho; Takahashi, Ayako; Kondo, Yuji; Chishima, Kayako; Toyokuni, Yoshiki
Abstract : Objective: The aim of this study was to identify disaster medical operation improvements from the 2016 Kumamoto Earthquake (Kumamoto Prefecture, Japan) and to extract further lessons learned to prepare for future expected major earthquakes. Methods: The records of communications logs, chronological transitions of chain of command, and team registration logs for the Disaster Medical Assistant Team (DMAT), as well as other disaster medical relief teams, were evaluated. Results: A total of 466 DMAT teams and 2, 071 DMAT team members were deployed to the Kumamoto area, and 1, 894 disaster medical relief teams and 8, 471 disaster medical relief team member deployments followed. The DMAT established a medical coordination command post at several key disaster hospitals to designate medical coverage areas. The DMAT evacuated over 1, 400 patients from damaged hospitals, transported medical supplies to affected hospitals, and coordinated 14 doctor helicopters used for severe patient transport. To keep constant medical and public health operations, DMAT provided medical coordination management until the local medical coordination was on-track. Several logistic teams, which are highly trained on operation and management of medical coordination command, were dispatched to assist management operation. The DMAT also helped to establish Disaster Coordination and Management Council at the prefectural- and municipal-level, and also coordinated command control for public health operations. The DMAT could provide not only medical assistance at the acute phase of the disaster, but also could provide medical coordination for public health and welfare. Conclusion: During the 2016 Kumamoto Earthquake, needs of public health and welfare increased enormously due to the sudden evacuation of a large number of residents. To provide constant medical assistance at the disaster area, DMAT, logistic teams, and other disaster medical relief teams must operate constant coordination at the medical headquarter command. For future expected major earthquakes in Japan, it will be required to educate and secure high enough numbers of disaster medical assistance and health care personnel to provide continuous medical and public health care for the affected area residents. Kondo H, Koido Y, Kawashima Y, Kohayagawa Y, Misaki M, Takahashi A, Kondo Y, Chishima K, Toyokuni Y. Consideration of medical and public health coordination – experience from the 2016 Kumamoto, Japan Earthquake. Prehosp Disaster Med . 2019;34(2):149–154